A scoping review of interventions for prevention and control of hypertension in India - Priyanka Pawar; Ritika Mukherjee; Archisman Mohapatra; Divita Sharma (Indian Journal of Public Health, 2023)
In India, hypertension (HTN) is a raging public health problem and demands contextualized strategies to combat it. However, there is a gap in indigenous research output on interventions related to HTN that work in the Indian context. We aimed to identify, describe, and systematically compile context-derived evidence for the prevention and control of HTN in adults in India across the community, health-care organization, and health policy domains by reviewing papers published over the past 10 years (January 2013–December 2022). Our goal was to prepare a ready-reckoner document that could serve as a baseline critique for HTN researchers, policymakers, and program managers for planning their respective courses of action. We searched for relevant literature published between January 2013 and December 2022, indexed in PubMed and Web-of-Science. We extracted information using the Template for Intervention Description and Replication checklist and used the Innovative Care for Chronic Conditions Framework for analysis and reporting. Only 33 articles emerged as “eligible.” The papers focused on community (39.4%), health-care organization (36.4%), and multi-domain (24.2%) strategies. Majority (69.7%) reported HTN control as an indicator to assess intervention effectiveness. Original research from India on HTN interventions is sparse. Thus, there is a need to promote research activities and publications that generate evidence for action in alignment with provisions and priorities of existing programs and policies, and with a focus on scalability and sustainability. Consequently, we call for increased attention to implementation science and research for HTN combat in India.